Bad breath and periodontal disease: how related are they? - Mel Rosenberg (Blackwell Synergy, 2006)
The article appearing in the current issue of the Journal of Clinical Periodontology on oral malodour in the Chinese population by Liu et al (2006) is the most recent in a series of articles on bad breath appearing in this Journal in recent years. This is a welcome sign. Bad breath is, for the most part, an oral condition. It is an awkward and embarrassing problem for millions, and can be a warning sign of medical and dental disease. Research on its diagnosis, aetiology, and treatment are of prime importance. The main purpose of this present editorial, however, is to stress that we still do not understand how periodontal health relates to the subject of bad breath.